Effect of 0.2% chitosan high molecule nanoparticle on the push-out bond strength of resin cement in post-restoration (An in-vitro study) - Kubbahseny RASENDREN; Trimurni ABIDIN (Dentistry Faculty, 2021)
ABSTRACT Debonding between post and resin cement often occurs due to inadequate smear layer removal.Currently, the wide use of Chitosan as an alternative irrigating solution can remove the smear layer. This studyaimed to determine the effect of 0.2% chitosan high molecule nanoparticle (CHMN) on the push-out bond strength ofresin cement in post-restoration and types of adhesion failure using the different irrigating solutions. Endodontictreatment was performed on 24 mandibular premolars, which were divided into four groups, namely group 1: 0.2%CHMN, group 2: 2.5% sodium hypochlorite (NaOCl) and CHMN, group 3: 5.25% NaOCl and CHMN, group 4: 2.5%NaOCl and EDTA 17%. The final restoration was done using prefabricated glass fiber posts, and each sample wassliced into three segments transversally with a thickness of 2 mm. A push-out test was performed with a universaltesting machine, and failure modes were observed under a stereomicroscope. Data were analyzed with a one-wayanalysis of variance (ANOVA), LSD, and Kruskal-Wallis tests. The results showed a significant difference in pushoutbond strength of resin cement in post-restoration between all groups. The Kruskal-Wallis test showed nosignificant difference between types of adhesion failure. In conclusion, 0.2% CHMN affects the push-out bondstrength of resin cement in post-restoration regardless of or without a combination of NaOCl. However, there wereno effects on the types of adhesion failure. Keywords: bond strength, 0.2% chitosan solution, endodontic irrigation, fiber post